The Relationship between New Learning Organization on Human Capital Readiness of Smes in Industry 4.0 - Saadah, Lailatul; Hendarman, Achmad Fajar (Green Publisher Indonesia, 2022)
Learning organization is one of the strategic plans that support the development of an organization. Based on organizational literacy known that learning organizations are aimed at developing human resources as the main driver in creating and developing an organization. Learning organization in the Era of Industry 4.0 forces a rapid change in organizational models and has no exception. Implementing diversity within organizations and change-resistant is a global challenge that critically required us to increase the readiness for change. The purpose of this study is to examine the relationship between new learning organizations and human capital readiness to continue to develop as a phenomenon at the individual level in SMEs in facing the era of industrial revolution 4.0. The population of this research is all SMEs in Indonesia. By using the probability sampling technique, namely simple random sampling, the minimum number of samples is 45 SMEs. The statistical method using multiple linear regression. The results showed that there is a significant relationship between new learning organizations (holistic people experience and agile, digitally enable infrastructure) on human capital readiness in Industry 4.0. The significance value ≤ 0.05. This means that the learning organizations especially the better holistic people experience and agile, digitally enable infrastructure, the higher the human capital readiness in a SMEs in the Era of Industry 4.0.